Moana finds the way - Amerikaner, Susan; Disney Enterprises (1996- ); Disney Storybook Artists; Penguin Random House; Random House Children's Books (New York Random House, 2016)
Moana sets sail in search of a fabled island, where she teams up with her hero, the legendary demigod Maui, to traverse the open sea
At head of title: Disney Moana
English Stories
Preschool-Grade 1
2
Keywords: Gods -- Juvenile fiction; Gods; JUVENILE FICTION / Action & Adventure; JUVENILE FICTION / Humorous Stories; JUVENILE FICTION / Media Tie-In; Adventure and adventurers -- Fiction; Gods -- Fiction; Ocean -- Fiction; Fiction; Juvenile works; Readers (Elementary); Readers (Elementary)